EVALUASI IMPLEMENTASI DISIPLIN DIRI PADA SISWA SMK TARUNA PEKANBARU - Fitri Yuliana; Donie Donie; Gusril Gusril; Arsil Arsil; Yovhandra Ockta (PAI RAFAH, 2023)
Based on the observations of researchers in the field, it can be seen that the application of self-discipline must still be improved and evaluated to be even better because self-discipline is one of the character education that is quite difficult to apply, especially in the discipline of school lesson tasks. This study aims to determine the evaluation of the implementation of self-discipline in students of SMK Taruna Pekanbaru. This type of research is a qualitative descriptive approach using the CIPP method (Context, Input, Process, and Product). The instruments used are observation, interviews, and documentation. The results of this study were found in terms of the context of program implementation as expected. This suitability can be seen from the background of the problem of evaluating this implementation which is clearly carried out, namely to improve the implementation of character education, especially in an attitude of respect, solidarity, tolerance, love for the motherland, nationalism, and responsibility. In terms of inputs, which include the resources owned, plans, and strategies in implementing self-discipline that has been applied in the environment of SMK Taruna Pekanbaru well.The Process aspect is as expected. This is due to the side of the person in charge, namely the principal, vice principal, and related teachers, as well as the TNI and Polri who are used as partners. There are many products and even all students come on time, enter classes according to the study hours schedule, wear full school attributes, and are neat in dressing.